Answer:
Area of the circle = 706.5 cm²
Step-by-step explanation:
Diameter = 30cm
Radius = 15cm
Area of the circle=πr²= 3.14(15)²= 3.14×225 = 706.5 cm²
Remark
You'll see it a whole lot easier if you make a substitution so that it looks like something you have already seen
Solution
let y = x^2
x^4 = x^2 * x^2
x^4 = y * y
x^4 = y^2
Now the expression becomes
y^2 + 8 y - 9 = z
(y + 9)(y - 1) = z
Now put the x^2 back in.
(x^2 + 9) ( x^2 - 1) = z
x^2 - 1 becomes x + 1 and x - 1. At this level x^2 + 9 can't be factored.
Answer
(x^2 + 9) (x + 1)(x - 1)
<span>Simplifying
x4 = 16
Solving
x4 = 16
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Simplifying
x4 = 16
Reorder the terms:
-16 + x4 = 16 + -16
Combine like terms: 16 + -16 = 0
-16 + x4 = 0
Factor a difference between two squares.
(4 + x2)(-4 + x2) = 0
Factor a difference between two squares.
(4 + x2)((2 + x)(-2 + x)) = 0
Subproblem 1
Set the factor '(4 + x2)' equal to zero and attempt to solve:
Simplifying
4 + x2 = 0
Solving
4 + x2 = 0
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + x2 = 0 + -4
Combine like terms: 4 + -4 = 0
0 + x2 = 0 + -4
x2 = 0 + -4
Combine like terms: 0 + -4 = -4
x2 = -4
Simplifying
x2 = -4
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve:
Simplifying
2 + x = 0
Solving
2 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + x = 0 + -2
Combine like terms: 2 + -2 = 0
0 + x = 0 + -2
x = 0 + -2
Combine like terms: 0 + -2 = -2
x = -2
Simplifying
x = -2
Sub-problem 3
Set the factor '(-2 + x)' equal to zero and attempt to solve:
Simplifying
-2 + x = 0
Solving
-2 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 2 + x = 0 + 2
Combine like terms: -2 + 2 = 0
0 + x = 0 + 2
x = 0 + 2
Combine like terms: 0 + 2 = 2
x = 2
Simplifying
x = 2Solutionx = {-2, 2}</span>
Answer:
Variables- x, y and z
Constants- 2 and 8
Coefficients- 3, 7, and 4
Step-by-step explanation:
Variables - The numbers we don't know/trying to find.
Constants- The numbers that remain fixed
Coefficients- The numbers in front of the variables